The prevalence and patterns of impacted canines in orthodontic patients: a CBCT study - Alfarra, Yahya H. Y.; Yusuf Noorani, Tahir; Ahmed Asif, Jawaad; Wan Ah- mad, Wan Muhamad Amir; Ahmad Rajion, Zainul (Ministry of Health and Universiti Brunei Darussalem, 2025)
Introduction: Although prevalence of impacted canines has been analyzed in prior studies, there is a lack of evidence about the prevalence of impacted canines in the Malaysian population to support such practices. Understanding the prevalence of impacted canines will enhance awareness, knowledge, and understanding of the importance of obtaining preventive and interventional treatment. The research aims to establish the impacted canine prevalence in orthodontic patients using cone beam computed tomography (CBCT). Materials and Methods: An examination of clinical records of 175 patients with canine impaction from January 1st, 2010, to November 30th, 2020 who had CBCT scans and visited dental clinics for orthodontic treatment was done to determine their prevalence. Descriptive statistics and Chi-square test analysis were carried out to evaluate the results. Results: The results suggested that the impacted canine prevalence was 17.5 %, with a female preponderance. Impacted canines occurred most frequently in Class I malocclusion subjects. In addition, canine impaction is more frequent on the left side than on the right. Unilateral impaction dominated bilateral impaction. Palatal impaction was more prevalent than buccal impaction, while maxillary canine impaction was more common than mandibular impaction. Conclusions: This study’s prevalence was higher than previously reported among other populations. The demography and gender have an effect on the incidence of impacted canines. These three-dimensional (3D) findings may provide clinical reference data for delivering information and education on impacted canines assessment and treatment.